MOTIVASI BELAJAR ANAK-ANAK NELAYAN DI MADRASAH ALIYAH - GUSTINA GUSTINA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
This article was proposed from research result about “Motivasi Belajar Anak-Anak Nelayan di Madrasah Aliyah” that had been done at MAN Sumpur Tanah Datar regency in 2011. This research was descriptive qualitative research. The researcher did obervation and interview to those students. Then, the researcher also interviewed the teacher in order to find out the students’ learning strategies, their part-time job after school, and time duration for working after school. The researcher also observed their daily activities at the school. From these activities, the researcher found that the students’ motivation in learning was still low because of many reasons: having lack of responsibility, always postponing doing the school works, being easy bored in learning, and having no interest to continue their study to the next level if they conduct their study at the school.Kata kunci: motivasi, energi belajar, anak nelayan